Synthesis and Characterization of Carbon Soot Particles Doped HPMC Polymer Composites - Gowtham, G.K.; Hegde, Vinayakprasanna N.; Meshk, Simin; Sukrutha, S.K.; Somashekar, R. (Journal of Research Updates in Polymer Science, 2015)
Biodegradable Hydroxyl propyl Methyl cellulose based polymer composites of various concentrations were prepared by doping carbon particles of kerosene soot. These composites were synthesized by employing simple solution casting method, to study the physical properties of the same. The analytical studies like XRD, AC conductivity, Tensile strength, Acoustic impedance, AFM and FTIR spectroscopy were carried out to characterize these composites. From the results it is seen that, the amorphous carbon particle disturbs the semi crystalline nature of the polymer by getting interstitial into polymer network. Further, this results in the characteristic changes of other physical parameters like tensile strength and AC conductivity. We have made an attempt to establish a structure property relation of such changes in the physical properties with that of microstructural parameters derived from XRD.